Unfelt : the language of affect in the British Enlightenment - Noggle, James (Cornell University Press, 2020)
"Offers a new account of feeling in British Enlightenment literature, showing how writers discreetly evoke a hidden layer of affect that supports and intensifies our strongly felt passions and sentiments"--